Calponin isoforms define the cell-type-specific organization and dynamics of actomyosin bundles - Kokate, Shrikant B.; Oshin, Afsana T.; Chua, Xiang Le; Chastney, Megan; Biswas, Parijat; Kogan, Konstantin; Tomberg, Teemu; Ivaska, Johanna; Lappalainen, Pekka (Elsevier, 2026)
Contractile actomyosin bundles, stress fibers, are important for cell migration, adhesion, morphogenesis, and mechanosensing. Calponin (CNN) family proteins are abundant stress fiber components, but their cellular functions and isoform-specific roles remain poorly understood. By depleting the three CNN isoforms (calponin-1 [CNN1], calponin-2 [CNN2], and calponin-3 [CNN3]) individually and collectively from U2OS cells, we show that CNNs are not negative regulators of myosin II, as previously suggested. Instead, we reveal that CNNs are critical regulators of stress fiber organization that control the distribution of actin filament cross-linker, α-actinin, along actomyosin bundles. Consequently, loss of CNNs dramatically reduced stress fiber thickness, increased their fragility, and impaired cell migration. Notably, we also identify isoform-specific roles for CNNs. The non-muscle CNN isoform CNN3 displays rapid turnover in stress fibers, enabling their dynamic remodeling, whereas the smooth-muscle isoform CNN1 exhibits stable association with stress fibers, supporting the formation of “smooth-muscle-like” thick and static actomyosin bundles. Our findings highlight CNNs as key regulators of stress fiber architecture, cell migration, and morphogenesis and provide new insights into the functional diversity of smooth-muscle and non-muscle CNN isoforms.